Analysis of Financial Feasibility of Construction of a Stainless-Steel Factory Capacity 1500 KTPA at PT. X in the IMIP Morowali Area - Oetomo, Dedy Setyo; Muslim, Mentari Nisaaul; Ramdhani, Rizki Fajar (Journal of Social Science and Business Studies, 2024)
This study was conducted to test the financial viability of building a stainless-steel plat on PT. X using method of financial analysis. The result of this study showed with net present value (NPV) US$ 901,972,225.60; Internal Rate of Return (IRR) of 15%; MARR 10%; Payback (PP) for 4 year and BEP US$372.39/ton for production 1,500,000/year. According to analytical research, the planned construction of the PT.X is a financially viable business to run and the project is acceptable. Each of these methods yields a distinct value for the computation of the payment duration. The investment proposal is deemed suitable based on the computation of the net present value, profitability index, and internal rate of return, as they meet the corresponding eligibility conditions. The inclusion of the time value of money is crucial when calculating the return period using NPV, ROI, and IRR. This ensures that the project's long-term benefits are taken into account. Consequently, it can be inferred that the assessment of the proposal's financial viability can be deemed acceptable or appropriate.